Optimizing rehabilitation strategies for elderly patients with femoral fracture – a prognostic perspective - Santoso, Eko Budi; Suwaryo, Putra Agina Widyaswara; Setianingsih, Endah; Asti, Arnika Dwi (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Femoral fractures in elderly people significantly impact their functional recovery and independence. Identifying reliable prognostic markers upon admission can facilitate optimal resource allocation and improve rehabilitation outcomes. This study aims to evaluate the predictive significance of pre-injury functional status, comorbid conditions, and cognitive function in determining independent living one year after injury. Material and methods. This retrospective observational study involved 132 consecutive patients over the age of 60 years who had suffered femoral fractures and were admitted to a specialized geriatric orthopedic unit. Prior to hospitalization, all patients were capable of independent living. Upon admission, three key prognostic indicators were evaluated: (1) the level of pre-injury performance in activities of daily living (ADL); (2) the absence of comorbidities that could hinder recovery; and (3) cognitive function, measured by a Pfeiffer mental questionnaire score above 7. The relationship between these prognostic factors and the ability to live independently one year after injury was examined using odds ratios (OR) with 95% confidence intervals (CI). Results. Among patients who possessed all three positive prognostic factors, 92% maintained independent living status after one year. In contrast, individuals with one, two, or three unfavorable predictors exhibited progressively lower rates of independent living, recorded at 96%, 82%, and 55%, respectively. The median duration of hospitalization within the first year varied across these groups, averaging 23, 74, 91, and 96 days, respectively. Furthermore, one-year mortality rates were found to be associated with the presence of comorbid conditions: 0% among those with only a femoral fracture, 14% in patients with one or two additional conditions, and 24% for those with three or more comorbidities. Conclusion. Simple and robust admission predictors including pre-injury ADL performance, absence of significant comorbidities, and preserved cognitive function can effectively estimate long-term functional outcomes in patients with femoral fracture in elderly people. These findings support the optimization of rehabilitation resources to improve recovery and promote independent living.